Ultrasonographic Assessment of Tendon Thickness, Doppler Activity and Bony Spurs of the Elbow in Patients with Lateral Epicondylitis and Healthy Subjects: A Reliability and Agreement Study - Krogh, T. P.; Fredberg, U.; Christensen, R.; Stengaard-Pedersen, K.; Ellingsen, T. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: Tennis elbow, also known as lateral epicondylitis (LE), is a common disorder often assessed by ultrasound. The aim of this study was to evaluate the ultrasonographic outcomes and methods used in LE research and clinical practice.Materials and Methods: This study was designed as an intra- and interobserver reliability and agreement study. Ultrasonographic examination of the common extensor tendon of the elbow was performed. The intraobserver study examined tendon thickness twice in 20 right elbows from 20 healthy individuals at an interval of 7 to 12 days. The interobserver study examined tendon thickness, color Doppler activity, and bony spurs in 18 right elbows in 9 healthy individuals and 9 patients with LE. Two trained rheumatologists performed the interobserver examinations with the same scanner on the same day. The main outcomes were intra- and interclass correlation (ICC) and agreement.Results: In the intraobserver study, the ICC with regard to tendon thickness ranged from 0.76 to 0.81, depending on the measurement techniques used. The agreement ranged from 0.06 to 0.13 mm. In the interobserver study, the tendon thickness ICC ranged from 0.45 to 0.65 and the agreement ranged from –0.17 to 0.13 mm. The ICC for color Doppler activity was 0.93, with agreement in 14/18 (78 %) of the cases. A perfect reliability was demonstrated for bony spurs, with an ICC of 1 and exact agreement in 18/18 (100 %) of the cases.Conclusion: Good to excellent reliability was obtained for all measurements. The ultrasonographic techniques evaluated in this trial can be recommended for use in both research and clinical practice.
Keywords: tendons; elbow; soft tissues; ultrasound; ultrasound color Doppler